Cashless Payment: A Perspective from Informal Family‑Run and Traditional Market Businesses in Ho Chi Minh City - Nguyen Viet , Bang; Nguyen Thi Hoang , Yen; Nguyen Viet , Bac; Nguyen Ho , Hai (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to analyze the factors influencing the adoption of cashless payment in small businesses at traditional markets and informal businesses in Ho Chi Minh City. Data was collected from 969 business owners, and Structural Equation Modeling (SEM) modeling was used to test the relationships in the model. The results show that the readiness to adopt technology positively influences the intention to transition to cashless payment, while organizational inertia, cash usage habits, and lack of trust in technology serve as significant barriers. Businesses with good technological infrastructure can more easily overcome inertia and adopt electronic payments. Policies should focus on enhancing technology readiness through training, infrastructure support, and encouraging the use of electronic payments. Additionally, organizational inertia should be minimized by building trust and demonstrating the benefits of cashless payments. This study provides valuable insights into the factors affecting the adoption of cashless payment in small businesses in Vietnam within the context of a rapidly developing digital economy.
Keywords: Cashless payments; Traditional market businesses; Informal family‑run